THE RULE OF LAW IN THE COUNTRIES OF THE WESTERN BALKANS AS A FOCUS OF THE ENLARGEMENT POLICY OF THE EUROPEAN UNION - Dragoslav Gluhović (STED Journal)
Back in 2018, the European Union adopted the Strategy of enlargement to the countries of the Western Balkans, which provided a potential time and reform framework for accession negotiations on the accession of these countries to the European Union. Strengthening the rule of law, the fight against corruption and organized crime are the cornerstones of accession negotiations and European integration processes for the countries of the Western Balkans. This paper provides an overview of the EU Strategy – Western Balkans from 2018, where the focus is on the initiative to strengthen the rule of law and the analysis of the situation in these countries from the point of view of the rule of law.